Observing and Modeling the Vertical Wind Profile at Multiple Sites in and above the Amazon Rain Forest Canopy - Raoni Aquino Silva de Santana; Cléo Quaresma Dias-Júnior; Roseilson Souza do Vale; Júlio Tóta; David Roy Fitzjarrald (Advances in Meteorology)
We analyzed the vertical wind profile measured at six experimental tower sites in dense forest in the Amazon Basin and examined how well two simple models can reproduce these observations. In general, the vertical wind profile below the canopy is strongly affected by the forest structure. From the forest floor to 0.65h (where h = 35 m is the average height of the forest canopy for sites considered), the wind profile is approximately constant with height with speeds less than 1 ms−1. Above 0.65 to 2.25h, the wind speed increases with height. Testing these data with the Yi and Souza models showed that each was able to reproduce satisfactorily the vertical wind profile for different experimental sites in the Amazon. Using the Souza Model, it was possible to use fewer input variables necessary to simulate the profile.